2014
DOI: 10.1016/j.mjafi.2014.03.001
|View full text |Cite
|
Sign up to set email alerts
|

The challenge in management of hemorrhagic shock in trauma

Abstract: a b s t r a c tTransfusion and resuscitation practices in trauma have undergone a sea change over the past decade. New understanding of transfusion physiology and experiences in military trauma over the last decade has identified key factors taken as challenges in trauma. The most important challenge remains acute traumatic coagulopathy (ATC) which sets in early after a trauma and spirals the patient into shock and continued bleeding. World wide trauma is the leading cause of mortality. More than 6 million dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 28 publications
1
16
0
9
Order By: Relevance
“…A short clotting time (low R) for example, may represent a disseminated intravascular coagulation state characterized by hypercoagulability and simultaneous fibrinolysis and hemorrhage; end organ injury can occur in this state. TEG has been shown to be able to diagnose and predict the likelihood of a patient developing a hyper‐coagulable state, which corresponds with the noted increase in mortality in this study.…”
Section: Discussionsupporting
confidence: 69%
“…A short clotting time (low R) for example, may represent a disseminated intravascular coagulation state characterized by hypercoagulability and simultaneous fibrinolysis and hemorrhage; end organ injury can occur in this state. TEG has been shown to be able to diagnose and predict the likelihood of a patient developing a hyper‐coagulable state, which corresponds with the noted increase in mortality in this study.…”
Section: Discussionsupporting
confidence: 69%
“…Previous research has shown that HS has a high rate of mortality; approximately 5.8 million people in the world die from trauma every year and 50% of these cases are due to HS (Jacob and Kumar, 2014;. HS is induced by many factors, including high rate of blood loss, severe vomiting or diarrhea, intestinal obstruction, or profuse sweating.…”
Section: Introductionmentioning
confidence: 99%
“…Uncontrolled bleeding leads to loss of coagulation factors and a later decrease in platelet counts. Hypovolemia due to intravascular blood volume loss and shock leads to tissue hypoperfusion and endothelial dysfunction [11]. Thrombomodulin (TM) expressed on vascular endothelium binds to thrombin forming a complex and it acts as an anticoagulant.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, currently there is a trend in major centers in Europe to avoid the use of blood components due to the high risk of adverse events. Possible complications associated with transfusion of blood components include transfusion-related acute lung injury (TRALI), transfusion associated circulatory overload (TACO), nosocomial infections, sepsis, transfusion-related immunomodulation (TRIM), and organ dysfunction [10, 11]. …”
Section: Introductionmentioning
confidence: 99%